Non-cost proposal to reduce educational-technological inequity during confinement in Chile - Yeomans Cabrera, María Mercedes; Silva Fuentes, Alicia (Revista de Estudios y Experiencias en Educación, 2022)
Introduction: In Chile, social inequity becomes a critical factor that prevents the successful implementation of an online curriculum due to the unbalanced distribution of technological resources. Even though during Covid-19 confinement there is a multichannel approach from the Ministry of Education to provide families with educational material, e-learning stands as the only available option for formal instruction. Objective: This study aimed to reduce educational-technological inequity during 2020 confinement in Chile through a non-cost feasible proposal. Material and Methods: The study was applied research under a mixed approach paradigm. In order to reach the main objective, two specific objectives were set: (1) To determine the contextual challenges related to technology that prevent online implementation of courses in Chile (2) To determine the popular technological resources in Chile that can be used for educational purposes. A checklist based on Aldowah’s questionnaire, and an analytic matrix were used to accomplish these objectives. Conclusions: A feasible contribution to educational-technological equity during 2020 confinement in Chile seems to be to use Facebook® for collaborative learning, lectures, oral presentations, reading comprehension, written production, discussion, creative learning, and feedback, since it can support all these types of activities, in a free-internet-access mode, supported for multi-device, which increases the opportunities of participation of all Chilean students in online classes.